Electrical properties of the anisotropic n-ТiО2/P-CdTe heterojunctions - Брус, Віктор Васильович; Ілащук, Марія Іванівна; Ковалюк, Захар Дмитрович; Мар’янчук, Павло Дмитрович; Ульяницький, Костянтин Сергійович; Кафанов, Анатолій Михайлович (Eastern-European Journal of Enterprise Technologies, 2012)
The electrical properties of the n-ТіО2/p-CdTe, prepared by deposition of TiO2 film onto freshly cleaved CdTe single crystal substrates were investigated. The electric current in the heterojunctions is induced by generation-recombination processes within the depletion region and tunneling of carriers